Social and health reasons for lime juice vaginal douching among female sex workers in Borno State, Nigeria - Abdulkarim G. Mairiga; Abubakar A. Kullima; Mohammed B. Kawuwa (AOSIS, 2010)
Background: Vaginal douching with lime juice and other agents has been perceived to enhance sexual excitement through sensations of vaginal dryness, tightness or warmth, as well as prevent sexually transmitted infections and restore and tighten the vagina after delivery. Its effectiveness as a contraceptive has also been reported. However, the social and health reasons/consequences of such a practice have not been adequately documented in the communities of Borno State, Nigeria. Objectives: This study aimed to determine the extent of, reasons for, and the reproductive health effects of, the use of lime juice for vaginal douching among the commercial sex workers (CSWs) in selected areas of the three senatorial regions of Borno State, Nigeria. Method: This was a community-based descriptive study conducted among female CSWs in selected communities of Borno State, Nigeria. A sample of 194 CSWs were randomly selected and interviewed on their sexual history and douching practices. Results: One hundred and twenty (62%) respondents admitted practicing vaginal douching with lime juice, with 85% having been CSWs for a period greater than three years. More than half douched for sexual pleasure, hygiene and contraception. Significantly more lime juice users had increased susceptibility to sexually transmitted infections (STIs) than non-users. Users had a higher prevalence of HIV infection than non-users. The Papanicouleaua (pap) smear test for cervical lesions also showed that moderate to severe dysplastic changes were more prevalent among limejuice users. Conclusion: Many CSWs in this community use lime juice for douching, for various reasons. Indications are that its use is associated with a higher prevalence of sexually transmitted diseases, including HIV infections and dysplastic cervical changes. Owing to confounding issues, such as the number of sexual partners, frequency of sexual exposure per day and the duration of exposure, it cannot, therefore, be deduced that douching with lime juice is the only reason for the higher prevalence of STIs and HIV. Nevertheless, there is an obvious need to mount extensive campaigns to educate the CSW on the possible risks of using such a practice.